Рівень економічної безпеки будівельних підприємств за інтегральним показником оцінки можливості рейдерського захоплення - Бєлєнкова, О. Ю.; Мацапура, О. В. (Ways to Improve Construction Efficiency, 2012)
In article the analysis of economic safety of the construction enterprises for a technique of an assessment of possibility of raider capture is carried out. The corresponding integrated indicator is calculated.